Responsible leadership practices amid COVID-19 to foster nurses’ occupational calling and curtail emotional exhaustion: a pre-and post-intervention effects analysis - Nilesh Kumar; Changfeng Wang; Muhammad Yaseen Bhutto (BMC Psychology)
Abstract Background The COVID-19 pandemic has placed an unprecedented strain on healthcare systems and their workers worldwide, including nurses. Frontline nurses experienced increased levels of stress and fatigue due to extensive and prolonged work hours, inadequate protective equipment, and fear of contracting the virus. This has resulted in a rise in emotional exhaustion among nurses. Therefore, it is crucial for organizations to address these challenges to sustain workers’ psychological wellbeing for better patient outcomes. Purpose/Objective Past studies have shown no link between responsible leadership (RL) and nurses’ occupational calling (OC) and emotional exhaustion (EE) amid COVID-9 or any situational setting. Therefore, this study evaluated the effectiveness of RL practices in improving the OC and alleviating the EE of nurses working in the COVID-19 ward of 94 government healthcare settings, including rural health centers (RHCs) and special COVID-19 response centers (CRCs), in Pakistan. Methodology The study employed a quasi-experimental pre-and post-design with responsible leadership-based interventions and a descriptive approach. Leadership practices included effective communication on COVID-19 guidelines, infection control measures, mental health support services, and others. An online questionnaire survey measured pre- and post-intervention effects using RL, OC, and EE scales. The sample comprised 289 frontline nurses, recruited via convenient sampling, who participated in a three-months program in the COVID-19 ward. Data analysis was conducted using AMOS and SPSS software, involving basic analysis and paired T-tests. Findings The paired t-test results revealed a significant improvement in nurses’ OC after the implementation of the RL intervention. The mean score for OC increased from 5.162 (SD = 1.151; t-value = 76.253) to 5.403 (SD = 1.054; t-value = 87.138; p < 0.001). Similarly, the intervention significantly reduced EE among nurses. The mean score for EE decreased from 4.386 (SD = 1.037; t-value = 71.879) to 3.614 (SD = 1.336; t-value = 45.987; p < 0.001). Both were statistically significant. Implications for nursing management Policymakers may need to consider the role of leadership practices in mitigating the negative effects of the pandemic on healthcare professionals’ well-being (i.e., EE and OC). Conclusions Leadership intervention can provide healthcare workers with the necessary skills and resources to cope with the challenges of their jobs, ultimately improving the quality of care provided to patients.